PEMILIHAN SUPPLIER BERDASARKAN INDEKS KAPABILITAS DENGAN KARAKTERISTIK TUNGGAL - Erik Bagus Prasetyo (Jurnal Manajemen Industri dan Logistik (JMIL), 2017)
Raw materials is a major requirement in the production process for manufacturing companies. in fulfilling the needs of raw materials for the production process, most manufacturing firms depends on suppliers. Supplier selection is an important part of manufacturing companies. From several supplier selection criteria, quality is one of the important criteria and it used in supplier assessment. Selecting suppliers based on the quality of their products will have a positive impact on manufacturing companies, such as increased profits through reduced operational costs and increased market share. In this study will compare two suppliers at manufacturing companies and choose one that has a higher capability value. The selection of suppliers is made using the yield index of Spk with a single characteristic. Supplier will be selected by comparing the yield ratio of two suppliers. Numerical calculations are performed on suppliers based on pH levels on the leather. The pH level on the leather will affect the color. A low pH may result color degradation earlier, whereas a high pH may result poor color matching.